ROLE OF VEGF A GENE POLYMORPHISM IN PREGNANT WOMEN WITH CHRONIC VIRAL HEPATITIS B WITH AND WITHOUT D AGENT - Akhmedova M.D., Tashpulatova Sh.A., Anvarov J.A., Atakhodjieva Kh.A., Maksudova Z.S. (Central Asian Journal of Medicine, 2025)
Vascular endothelial growth factor (VEGF) and its receptors play an important role in regulating angiogenesis. The aim of the study was to investigate the VEGF A gene polymorphism in pregnant women with chronic viral hepatitis B (CVHB) with and without the D agent. A prospective observational study was conducted among 188 pregnant women aged 18 to 45 years. The main group included 67 pregnant women with complicated pregnancy outcomes: 32 with CVHB and the D agent, and 35 without the D agent. The comparison group consisted of 70 pregnant women with uncomplicated pregnancies: 23 with CVHB and the D agent, and 47 without the D agent. The control group included 51 healthy pregnant women without a history of chronic viral hepatitis. The distribution and haplotypes of the -2578 C/A polymorphic locus (rs699947) of the VEGF A gene were studied. Changes in the distribution of the studied genotype were associated with the risk of pregnancy complications: the CA genotype demonstrated a protective role in uncomplicated pregnancies in women with CVHB with and without the D agent, while the AA genotype, on the contrary, was associated with an increased risk of pregnancy complications. The reduced frequency of the heterozygous CA genotype and the predominance of the AA genotype among pregnant women indicated a higher probability of adverse pregnancy outcomes.